Solve the differential equation by separation of variables.
(x^3 + 2)y = x(y^4 + 3)y’ ; at x = 1 and y = 1
Let us solve the differential equation by separation of variables:
"(x^3 + 2)y = x(y^4 + 3)y'"; at "x = 1" and "y = 1". It follows that "(x^3 + 2)y = x(y^4 + 3)\\frac{dy}{dx}," and hence "\\frac{x^3 + 2}{x}dx = \\frac{y^4 + 3}{y}dy." It follows that "\\int\\frac{x^3 + 2}{x}dx = \\int\\frac{y^4 + 3}{y}dy," and hence "\\int(x^2+\\frac{2}{x})dx = \\int(y^3+\\frac{3}{y})dy." Therefore, the general solution is "\\frac{x^3}{3}+2\\ln|x|=\\frac{y^4}4+3\\ln|y|+C." Since "y=1" for "x=1", we get that "\\frac{1}{3}=\\frac{1}4+C," and thus "C=\\frac{1}{3}-\\frac{1}4=\\frac{1}{12}." We concludwe that the solution is "\\frac{x^3}{3}+2\\ln|x|=\\frac{y^4}4+3\\ln|y|+\\frac{1}{12}."
Comments
Leave a comment